Experimental study of temperature mode of a fire in a cable tunnel - Nuianzin, Oleksandr; Pozdieiev, Serhii; Hora, Viacheslav; Shvydenko, Andrii; Samchenko, Taras (Eastern-European Journal of Enterprise Technologies, 2018)
We established, based on the conducted research into a change in temperature in the cable tunnel during fire, that in the combustion zone the temperature grows faster in comparison with the standard temperature mode of a fire. This indicates the need for testing fire resistance of construction structures of cable tunnels using the temperature regime that differs from the standard one. During the research, a scientifically-substantiated sequence of procedures was created, with a detailed selection of equipment and test samples, in order to provide reliable experimental data when studying the temperature regime of a fire in a cable tunnel. Thus, based on the results of our experimental study, we determined the temperature modes of a fire in different zones of the cable tunnel using the proposed procedure. The highest temperature is observed directly in the combustion zone. In the fire zone next to cables, it is 700‒900 °C; between a fire center zone and the opening for the discharge of combustion products, it is in the range of 250‒500 °C. In the zone between a fire center and the place of air head, the temperature reaches 80‒150 °C. The rate of flame propagation, in terms of direction, coincides with the direction of air flow twice as faster as in the opposite direction. Thus, we can argue that the research results obtained could be the basis for constructing mathematical models that describe fires in cable tunnels and might be used for the engineering estimation of fire resistance of building structures of cable tunnels.